Theoretical criminology: from modernity to post-modernism - Morrison, Wayne (Cavendish Publishing, 1995)
1. Narrating the mood of the times : confusion, self-doubt, and ambivalence -- 2. The problem of modernity -- 3. The theorists of modernity : an introduction to Max Weber, Karl Marx, Emile Durkheim and Freidrich Nietzsche -- 4. The problem of classical criminology : stabilising disorder through law, or how to achieve the rule of law and hide the chaos of early modernity -- 5. Reading the texts of classical criminology : beyond mere command into systematic legitimation -- 6. Criminological positivism I : the search for the criminal man, or the problem of the duck -- Criminological positivism II : psychology and the positivisation of the soul -- 8. Criminological positivism III : statistics, quantifying the moral health of society and calculating nature's laws -- 9. Positivism and the dream of organised modernity -- 10. Morality, normalcy and modernity : the moral intensity of everyday life -- 11. Locality and criminology : from the polis to the post-modern city -- 12. Criminology and the culture of modernity -- 13. Culture and crime in the post-modern condition -- 14. Labelling theory, and the work of David Matza -- 15. Crime and the existentialist dilemma -- 16. Modernity, gender and crime : from the biological paradigm into feminist interpretations -- 17. Contemporary social stratification and the development of the underclass -- 18. Building criminological theory in post-modernism.